Innovative video on compound interest / Siti Fairus Fuzi … [et al.] - Fuzi, Siti Fairus; Jusoh, Nordianah; Zainudin, Siti Nursyahira; Abdul Halim, Bushra; Jama, Siti Ramizah; Zahidi, Nurul Emyza (Faculty of Computer and Mathematical Sciences, 2023)
The coronavirus disease 2019 (COVID-19) is still infecting the world population even after mass vaccination programs are being conducted by most countries. Countries in the world have their own measures to curb and control the spread of the virus. Both the COVID-19 pandemic and measures of its control have negatively affected the mental health of the citizens. Among the affected citizens are the university students who are facing great challenges due to both pandemic and their academic lives. The situation also challenged the educational sector worldwide. During the COVID-19 health crisis in Malaysia, the Movement Control Order (MCO) triggered the need for more innovative video lessons to cater for e-learning classes. The primary goal of this work is to create innovative video lessons for the diploma students' courses Mathematics with Business Applications (MAT111) and Business Mathematics (MAT112). Our current study revealed that there was a statistically significant higher anxiety level if students experienced unstable internet in their place of stay. The results suggest students who experienced challenges in ODL had higher chances of developing anxiety. As a result, the video is practical because it is published on YouTube and accessible to students who have registered for the class. Students can review the usefulness of the video lessons in class and after class for 14 weeks during one academic semester session. Furthermore, the application's usefulness is that the capabilities are incorporated to enhance the learning process, it's available 24/7 and accessible from anywhere using a mobile smartphone. The video was created with Sparkol, Create Studio, CrazyTalk Animator, and Wondershare Filmora X, and it was stored and published on YouTube. The video contains useful information about compound interest and uses simple explanations and tutorials to ensure that everyone understands the topic. This product helps students grasp compound interest, lowering failure rates in business mathematics. It's also valuable for non-UiTM students interested in learning business mathematics.